2018
DOI: 10.1159/000494240
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 Inhibited Diabetes-Induced Phenotypic Switching of Vascular Smooth Muscle Cells Through Activating Autophagy

Abstract: Background/Aims: The phenotype switching of vascular smooth muscle cells (VSMCs) was associated with the onset or progression of the atherogenic process in type 2 diabetes mellitus (T2DM). Alprostadil (Prostaglandin E1, PGE1) as a bioactive drug had a protective effect on vascular function. However, it is unknown whether PGE1 inhibited the phenotype switching in VSMCs via autophagy, which played a protective role in the vascular complications of diabetes. Methods: The phenotype switching was induced by high gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In diabetic rat carotid arteries, expression of smooth muscle-specific markers including ACTA, myosin heavy chain, and calponin-1 is significantly decreased [45]. Others also have found that contractile smooth muscle-specific markers are decreased in response to hyperglycemia [46]. Along the lines with these results, we showed that both high Pi and HG triggered the loss of SMC-specific markers, and the HG condition aggravated high Pi-induced downregulation of SMC markers.…”
Section: Discussionsupporting
confidence: 84%
“…In diabetic rat carotid arteries, expression of smooth muscle-specific markers including ACTA, myosin heavy chain, and calponin-1 is significantly decreased [45]. Others also have found that contractile smooth muscle-specific markers are decreased in response to hyperglycemia [46]. Along the lines with these results, we showed that both high Pi and HG triggered the loss of SMC-specific markers, and the HG condition aggravated high Pi-induced downregulation of SMC markers.…”
Section: Discussionsupporting
confidence: 84%
“…Recent studies have shown that autophagy induction inhibits both the endothelial dysfunction (Fetterman, et al, 2016;Y. Xie, et al, 2011) in endothelial cells from diabetic patients and phenotypic switching of VSMCs in diabetic vascular lesions (An, Li, Wei, Li, & Xu, 2018;Qiu, et al, 2018). These studies demonstrate a protective role of autophagy in diabetic vascular disorders.…”
Section: Autophagy In Diabetic Medial Calcificationmentioning
confidence: 80%
“…Initially, rats were randomly divided into two groups: HFD group and normal diet group. Rats in HFD group were fed HFD for 4 weeks, and then given an intraperitoneal injection of a single dose of STZ (40 mg/kg) (dissolved in citrate buffer at pH 4.5, Saiguo Biotechnology, Guangzhou, China) to induce T2DM (An et al, 2018). Rats in normal diet group were fed chow diet for the same period, and given an intraperitoneal injection of citrate buffer.…”
Section: Animals and Experimental Designmentioning
confidence: 99%